Performance of High Volume Fly Ash Concrete in Structural Applications - Puneet Kaura; P N Ojha; Brijesh Singh (Journal of Building Materials and Structures)
Application of high volume fly ash concrete is still not advocated by construction fraternity due to lack of standardisation. In India, fly ash as a pozzolanic material can be used in manufacturing of Portland Pozzolana cement and composite cement with a maximum limit of 35%. Present study had been carried out at various percentages of fly ash and a detailed mechanical and durability study was conducted. In this paper, concrete mixes were designed at two water binder ratio with 30%, 35%, 40% and 50% fly ash content. Mechanical behaviour of concrete was studied through tests like compressive strength (at age of 1, 3, 7, 28, 56 and 90 days) and flexure strength (at an age of 7, 28 and 90 days). Durability aspect of high volume fly ash concrete mixes were determined through various test like RCPT, non-steady state chloride migration, bulk conductivity, accelerated carbonation etc. and comparison is made with control mixes (i.e. concrete made with OPC). Alkali silica reactivity (ASR) study was also carried out at 30%, 35%, 40% and 50% fly ash content using reactive aggregates. It was quite evident from test results that strength characteristics of high volume flyash concrete mix made with 50% flyash content was remarkably lower than that of all other concrete mixtures. High volume flyash concrete mix designed at 40% flyash content had shown exemplarily performance in comparison to other high volume flyash concrete mixes as well as control mixes. Flyash content was found to most significant parameter influencing rate of carbonation.